2022
DOI: 10.3390/ph15030308
|View full text |Cite
|
Sign up to set email alerts
|

In Silico and In Vitro Identification of Pan-Coronaviral Main Protease Inhibitors from a Large Natural Product Library

Abstract: The main protease (Mpro or 3CLpro) in coronaviruses represents a promising specific drug target as it is essential for the cleavage of the virus polypeptide and has a unique cleavage site that does not exist in human host proteases. In this study, we explored potential natural pan-coronavirus drugs using in vitro and in silico approaches and three coronavirus main proteases as treatment targets. The PyRx program was used to screen 39,442 natural-product-like compounds from the ZINC database and 121 preselected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 76 publications
4
24
0
Order By: Relevance
“…These results are in accordance with the literature because Z -rosmarinic acid is reported to be not stable enough to be isolated in a pure form. 13 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in accordance with the literature because Z -rosmarinic acid is reported to be not stable enough to be isolated in a pure form. 13 …”
Section: Resultsmentioning
confidence: 99%
“…Recently, E -rosmarinic acid has been reported to inhibit SARS-CoV-2 replication and SARS-CoV-2 3CL pro 13 However, the activity of the Z -isomer has not been reported yet. This prompted us to investigate and compare the 3CL pro inhibitory potential of compounds 1 and 2 ( 2 Z and 2 E ) ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because we and others [12,14] showed that ART is not the most likely anti-SARS-CoV-2 therapeutic phytochemical in A. annua extracts, questions remain regarding the identity of these non-ART phytochemicals. To resolve that question, several groups have used in silico approaches [22,23]. Tang et al screened the Traditional Chinese Medicines for systems Pharmacology Databased and Analysis Platform to identify all phytochemicals reportedly in A. annua then ranked them according to oral bioavailability and drug likeness (OB and DL, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…The lack of vaccines and antivirals is partly due to a poor understanding of the structural characteristics of the viral proteins that are involved in viral infection and replication [ 89 ]. Teams all over the world are using MST to study CoV since fast screening on large libraries can be performed [ 90 ]. Here we will highlight specific cases to illustrate the benefit of the methodology.…”
Section: Case Studiesmentioning
confidence: 99%